Peran Digital Transformation dan Teknologi Digital dalam Memacu Corporate Entrepreneurship: Tinjauan Literatur - Umar, Haniatur Rofiqoh; Syafitri, Dinda; Winarno, Agung; Kusdiyanti, Heny (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to analyze how digital transformation and digital technology drive corporate entrepreneurship in incumbent companies. The method used is a narrative literature review of books, articles, and academic journals published between 2018 and 2025 that discuss digital transformation, the utilization of digital technology, and corporate entrepreneurship mechanisms. The study results indicate that digital technologies—such as cloud computing, big data analytics, artificial intelligence, and collaborative platforms—serve as an innovation infrastructure enabling rapid experimentation, cross-functional collaboration, and data-driven decision-making. This technology has been proven to foster intrapreneurial behavior and strengthen the process of creating new value. Beside technological aspects, the effectiveness of corporate entrepreneurship is significantly influenced by organizational factors such as ambidextrous leadership, mature digital governance, and agile-based intrapreneurship programs. External collaboration thru partnerships with startups also plays a crucial role in accelerating innovation, as long as the organization can manage the integration of knowledge and differences in institutional logic. Overall, this review confirms that digital transformation and corporate entrepreneurship are two mutually reinforcing strategic agendas for enhancing organizational competitiveness. Harmonious integration between digital technology, governance structures, agile culture, and visionary leadership is key to maximizing the potential of corporate entrepreneurship in the digital age.